Lessons learnt from an unsuccessful clinical trial of homœopathy - Jansen, G.R.H.J.; Veer, A.L.J.v.d.; Hagenaars, J.; Kuy, A.v.d. (British Homeopathic Journal, 1992)
In a randomized, double-blind study, the effects of individualized homœopathy in patients suffering from proctocolitis were investigated. The study was controlled against conventional therapy and placebo.Individually indicated homoœopathic medicines were prescribed in the 30c, 200c or 1,000c potencies.The researchers did not succeed in attracting sufficient numbers of participants to arrive at statistically significant conclusions. The total number of patients in the three combined groups was only 20, which was far below the target figure. The causes of this are discussed.Bowel habit and subjective parameters were assessed by a weekly health calendar. This calendar had not been previously validated. The conventional group scored best: eight out of ten patients completed the year of research and improved both with regard to their proctocolitis and their general well-being.
Keywords: Double-blind trial; Homœopathy; Individualization; Proctocolitis; Methodology; Netherlands